Malaysian ESL students’ perceptions on the usability of a mobile application for grammar test: a case study of ESL undergraduates in Universiti Sains Malaysia - Malini Ganapathy; Munir Shuib; Siti Norbaya Azizan (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
With the proliferation of mobile technologies nowadays, English language educators and instructors globally are increasingly looking into the potential of mobile learning as pedagogical practice to teach the language, including as a tool to test students’ grammatical ability. However, users’ perception on the usability of such advanced approach in education is critical to a successful mobile learning implementation. While there is a considerable enthusiasm for incorporating mobile technologies in English language education, there is a paucity of research evidence about whether mobile-based test is perceived as usable by English language students in Malaysia. The purpose of this paper is to examine Malaysian English as a Second Language (ESL) students’ perception on the usability of a mobile application for grammar test; namely MyGrammarTest (MyGraTe) App. The App was developed by a mobile learning research team from Universiti Sains Malaysia (USM) who studied the development of an intelligent mobile learning tool that can map grammar learning content to their learning style preferences. Upon successful development, the MyGraTe App prototype was piloted on a group of undergraduate students who undertook ESL courses in USM. Then, a questionnaire consisting of items adapted from the System Usability Scale (SUS) by Brooke (1986) was distributed to respondents to gain input on the perceived usability of the App. Findings from this study provide several important insights on the usability of mobile applications as learning support tools for English language learning, specifically in testing students’ grammatical ability.